The Effect of Compensation and Career Development on Job Hopping in the Banking Sector - Wulandari, Novita; Athoillah (Research Horizon, 2025)
This study aims to analyses the influence of compensation, career development, and employee engagement on job hopping, as well as the mediating role of employee engagement in the relationship between compensation and career development on job hopping. This study uses a quantitative approach with a purposive sampling method on 160 employees of the banking sector in DKI Jakarta. Data testing was carried out using the SmartPLS analysis tool through validity, reliability, and hypothesis tests. The results of the study show that compensation, career development, and employee engagement have a significant effect on job hopping. Career development also has a significant effect on employee engagement, and employee engagement has been shown to play a significant mediating variable in the relationship between career development and job hopping. However, no significant relationship was found between compensation for employee engagement, and employee engagement did not mediate the relationship between compensation and job hopping. These findings emphasize the importance of career development and employee engagement in managing job hopping tendencies, while compensation in this context has no direct or indirect relationship through employee engagement.